2021
DOI: 10.1038/s41562-021-01176-8
|View full text |Cite
|
Sign up to set email alerts
|

Paranoia and belief updating during the COVID-19 crisis

Abstract: The COVID-19 pandemic has made the world seem less predictable. Such crises can lead people to feel that others are a threat. Here, we show that the initial phase of the pandemic in 2020 increased individuals' paranoia and made their belief updating more erratic. A proactive lockdown made people's belief updating less capricious. However, state-mandated mask-wearing increased paranoia and induced more erratic behaviour. This was most evident in states where adherence to mask-wearing rules was poor but where ru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
120
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 53 publications
14
120
0
1
Order By: Relevance
“…Finally, researchers have indicated that emotions could mediate the relationship between institutional trust and prevention behaviors ( Min et al, 2020 ). Amid the COVID-19 pandemic, both paranoia and conspiracy beliefs have changed over time ( Suthaharan et al, 2021 ). Given the potential influences of emotion, cognition, and personality on the association between trust and preventive practices during the pandemic, future studies can further explore this issue by measuring the related indicators during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, researchers have indicated that emotions could mediate the relationship between institutional trust and prevention behaviors ( Min et al, 2020 ). Amid the COVID-19 pandemic, both paranoia and conspiracy beliefs have changed over time ( Suthaharan et al, 2021 ). Given the potential influences of emotion, cognition, and personality on the association between trust and preventive practices during the pandemic, future studies can further explore this issue by measuring the related indicators during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As well as being at the receiving end of therapies, people with a history of psychosis possess valuable knowledge that could be useful in helping others who do not have the same lived expertise (Florence et al, 2021). The world experienced unusual psychosis-like paranoia and erratic thinking at the start of the pandemic (e.g., Suthaharan et al, 2021 ; Lopes et al, 2020 ), with new mental health difficulties in people who did previously not have them (e.g., D’Agostino et al, 2021 ). Experts by experience should be employed to advise health professionals on interventions for those who have suffered as a result of the pandemic.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Paranoia was found to be unrelated to betrayal aversion-when one has a higher aversion to risky situations where outcomes are contingent upon social factors compared to non-social factors, which does not support the coalitional cognition model [17]. Instead, paranoia may arise from domain-general mechanisms of uncertainty weighted belief updating [18,19]. Here we attempted an explicit separation of social and non-social influences to belief updating and paranoia in order to shed light on whether paranoia arises from socially-specific processes or domain-general cognitive mechanisms.…”
Section: Introductionmentioning
confidence: 99%